Saat bahasa arab terasa menakutkan: mengapa mahasiswa membutuhkan metode belajar yang humanis - hasanah, nur hidayatul (Maliki Interdisciplinary Journal, 2026)
Arabic is often perceived as a difficult and intimidating subject by many university students. This perception is not solely caused by the linguistic complexity of Arabic, but also by learning experiences that tend to overlook students’ emotional and psychological needs. This article aims to provide a reflective discussion on why university students need a more humanistic approach in learning Arabic. The discussion highlights the relationship between teaching approaches, classroom atmosphere, and students’ motivation and confidence in using Arabic actively. A humanistic approach is viewed as an effort to create a safe, supportive, and dialogical learning environment in which students feel comfortable making mistakes as part of the learning process. By positioning students as active subjects with diverse backgrounds and learning needs, Arabic learning can become more meaningful and enjoyable. This article is expected to serve as a reflective reference for Arabic language educators in developing teaching practices that focus not only on language mastery but also on students’ overall learning experience.